2015
DOI: 10.1021/acs.jnatprod.5b00246
|View full text |Cite
|
Sign up to set email alerts
|

Vanillic Acid Inhibits Inflammatory Pain by Inhibiting Neutrophil Recruitment, Oxidative Stress, Cytokine Production, and NFκB Activation in Mice

Abstract: Vanillic acid (1) is a flavoring agent found in edible plants and fruits. It is an oxidized form of vanillin. Phenolic compounds form a substantial part of plant foods used as antioxidants with beneficial biological activities. These compounds have received considerable attention because of their role in preventing human diseases. Especially, 1 presents antibacterial, antimicrobial, and chemopreventive effects. However, the mechanisms by which 1 exerts its anti-inflammatory effects in vivo are incompletely und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(108 citation statements)
references
References 52 publications
5
97
0
Order By: Relevance
“…In conclusion, our findings suggest that PDK2 and PDK4 are indispensable in the pathogenesis of acute inflammation and subsequent nociception. At the site of inflammation, significantly enhanced expression of Pdk2 and Pdk4 mediates plasma extravasation and the activation and recruitment of neutrophils that can amplify inflammation and subsequent nociception via production of proinflammatory mediators (Liou et al, 2013;Jha et al, 2014;Tecchio et al, 2014;Calixto-Campos et al, 2015) and lactic acid (Sheikh et al, 2000;Bensel et al, 2011;Jha et al, 2015b), as reported earlier. As a consequence of peripheral noxious stimulation, the spinal dorsal horn displays glial activation as well as neuronal excitability, thereby leading to the central sensitization that amplifies nociceptive behaviors.…”
Section: Discussionmentioning
confidence: 78%
“…In conclusion, our findings suggest that PDK2 and PDK4 are indispensable in the pathogenesis of acute inflammation and subsequent nociception. At the site of inflammation, significantly enhanced expression of Pdk2 and Pdk4 mediates plasma extravasation and the activation and recruitment of neutrophils that can amplify inflammation and subsequent nociception via production of proinflammatory mediators (Liou et al, 2013;Jha et al, 2014;Tecchio et al, 2014;Calixto-Campos et al, 2015) and lactic acid (Sheikh et al, 2000;Bensel et al, 2011;Jha et al, 2015b), as reported earlier. As a consequence of peripheral noxious stimulation, the spinal dorsal horn displays glial activation as well as neuronal excitability, thereby leading to the central sensitization that amplifies nociceptive behaviors.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies also noted vanillin's anti-inflammatory property [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Moreover it was proved that also vanillic acid regulated ulcerative colitis via inhibition NF-κB p65 activation and reduction in pro-inflammatory cytokines production; IL-1, IL-6 and TNF-α [33].…”
Section: Discussionmentioning
confidence: 93%
“…VA is also a constituent of wine, vinegar, and argan oil (20). It has antioxidant, antiinflammatory, and anticancer pharmacologic properties (21,22). A study by Hsu and Yen (23) showed that VA caused inhibition of intracellular TG in 3T3-L1 adipocytes.…”
mentioning
confidence: 99%